Economic valuation of informal care provided to people after a myocardial infarction in France - Hugo Rabier; Hassan Serrier; Anne-Marie Schott; Nathan Mewton; Michel Ovize; Norbert Nighoghossian; Antoine Duclos; Cyrille Colin (BMC, 2019)
Abstract Background The aim of this study was to estimate the mean cost per caregiver of informal care during the first year after myocardial infarction event in France. Methods We used the Handicap-Santé French survey carried out in 2008 to obtain data about MI survivors and their caregivers. After obtaining the total number of informal care hours provided by caregiver during the first year after MI event, we estimated the value of informal care using the proxy good method and the contingent valuation method. Results For MI people receiving informal care, an annual mean cost was estimated at €12,404 (SD = 13,012) with the proxy good method and €12,798 (SD = 13,425) with the contingent valuation method per caregiver during the first year after myocardial infarction event. Conclusions The present study suggests that informal care should be included more widely in economic evaluations in order not to underestimate the cost of diseases which induce disability.